Pengaruh motivasi kerja terhadap disiplin kerja sebagai upaya meningkatkan komitmen organisasi (studi pada karyawan UD. Karya Abadi Kediri) - Puspita Ambarwati Ayu Kinanti; Bayu Cahyoadi (Jurnal Pendidikan Ekonomi (JUPE), 2025)
Increasing organizational commitment is a major component in a company. This is because, to find out an employee’s organizational commitment; what must be considered is work motivation and work discipline in other to foster accountability and strong synergy for the company’s success. Scientific purposes of this research is to determine the effect of work motivation on organizational commitment of employees of UD. Karya Abadi Kediri; to determine the effect of work motivation on work discipline of employees of UD. Karya Abadi Kediri; and to determine the effect of work discipline on organizational commitment of employees of UD. Karya Abadi Kediri. Data collection using a questionnaire of 106 respondents. This research uses Path Analysis using the assistance of IBM SPSS Statistics for windows software. Empirical findings indicate that work motivation has a positive and significant effect on organizational commitment of employees of UD. Karya Abadi Kediri; work motivation has a positive and significant effect on work discipline of employees of UD. Karya Abadi Kediri; and work discipline has a positive and significant effect on organizational commitment of employees of UD. Karya Abadi Kediri.